Valuation of Environmental Goods: Travel Cost Approach - Bhusal, Tara Prasad (Economic Journal of Development Issues, 2010)
There are basically two methods of the valuation of the environmental goods: the market based approach and the non-market based approaches. When a market exists, it is relatively easy to apply market-based techniques to measure value. But when market information relating to prices and quantities is not available to estimate the value of the resource or resource service, we use non-market valuation methods. The most widely recognized non- market techniques is the travel cost method. The simplest version of the Travel Cost Method (TCM) is the zonal method. The main objective of present article is to describe the concept TCM to measure the value of environmental goods with a hypothetical example. This article also reviews available literatures to develop the logical understanding of the techniques of the TCM. Key words: Environmental goods; Valuation; Non-market; Market-based; Travel cost; Zonal method Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 155-166